Detection of an endogenous urinary biomarker associated with CYP2D6 activity using global metabolomics - Tay-Sontheimer, Jessica; Shireman, Laura M; Beyer, Richard P; Senn, Taurence; Witten, Daniela; Pearce, Robin E; Gaedigk, Andrea; Gana Fomban, Cletus L; Lutz, Justin D; Isoherranen, Nina; Thummel, Kenneth E; Fiehn, Oliver; et al. (Pharmacogenomics, 2014)
We sought to discover endogenous urinary biomarkers of human CYP2D6 activity. Healthy pediatric subjects (n = 189) were phenotyped using dextromethorphan and randomized for candidate biomarker selection and validation. Global urinary metabolomics was performed using liquid chromatography quadrupole time-of-flight mass spectrometry. Candidate biomarkers were tested in adults receiving fluoxetine, a CYP2D6 inhibitor. A biomarker, M1 (m/z 444.3102) was correlated with CYP2D6 activity in both the pediatric training and validation sets. Poor metabolizers had undetectable levels of M1, whereas it was present in subjects with other phenotypes. In adult subjects, a 9.56-fold decrease in M1 abundance was observed during CYP2D6 inhibition. Identification and validation of M1 may provide a noninvasive means of CYP2D6 phenotyping.